Prolactin regulation of oxytocin neurone activity in pregnancy and lactation - Augustine, Rachael A. (J Physiol, 2017)
KEY POINTS: During lactation, prolactin promotes milk synthesis and oxytocin stimulates milk ejection. In virgin rats, prolactin inhibits the activity of oxytocin‐secreting neurones. We found that prolactin inhibition of oxytocin neurone activity is lost in lactation, and that some oxytocin neurones were excited by prolactin in lactating rats. The change in prolactin regulation of oxytocin neurone activity was not associated with a change in activation of intracellular signalling pathways known to couple to prolactin receptors. The change in prolactin regulation of oxytocin neurone activity in lactation might allow coordinated activation of both populations of neurones when required for successful lactation. ABSTRACT: Secretion of prolactin for milk synthesis and oxytocin for milk secretion is required for successful lactation. In virgin rats, prolactin inhibits oxytocin neurones but this effect would be counterproductive during lactation when secretion of both hormones is required for synthesis and delivery of milk to the newborn. Hence, we determined the effects of intracerebroventricular (i.c.v.) prolactin on oxytocin neurones in urethane‐anaesthetised virgin, pregnant and lactating rats. Prolactin (2 μg) consistently inhibited oxytocin neurones in virgin and pregnant rats (by 1.9 ± 0.4 and 1.8 ± 0.5 spikes s(−1), respectively), but not in lactating rats; indeed, prolactin excited six of 27 oxytocin neurones by >1 spike s(−1) in lactating rats but excited none in virgin or pregnant rats (χ(2) (2) = 7.2, P = 0.03). Vasopressin neurones were unaffected by prolactin (2 μg) in virgin rats but were inhibited by 1.1 ± 0.2 spikes s(−1) in lactating rats. Immunohistochemistry showed that i.c.v. prolactin increased oxytocin expression in virgin and lactating rats and increased signal transducer and activator of transcription 5 phosphorylation to a similar extent in oxytocin neurones of virgin and lactating rats. Western blotting showed that i.c.v. prolactin did not affect phosphorylation of extracellular regulated kinase 1 or 2, or of Akt in the supraoptic or paraventricular nuclei of virgin or lactating rats. Hence, prolactin inhibition of oxytocin neurones is lost in lactation, which might allow concurrent elevation of prolactin secretion from the pituitary gland and activation of oxytocin neurones for synthesis and delivery of milk to the newborn.